Strategi Pemasaran Sulaman Karawo Di Destinasi Pariwisata Gorontalo - Srilian Laxmiwaty Dai; Irma e Charisma Hatibie (JURNAL DESTINASI PARIWISATA, 2021)
This research analyzes Karawo embroidery's developmentas one of Gorontalo's cultural heritagesat Gorontalo tourist destinations. Culture is an identity of a region that becomes a heritage through generations. Culture also becomes a crucial part in the tourism industry because it is interesting for tourists curiosity about new and unique things. On the other side, tourism is also an industry to preserve culture.Therefore, it is essential to figure out the development position of Karawo embroideryso thatKarawo can be existed to develop Gorontalo tourism industry.This descriptive qualitative research employs Product Life Cycle Theory. This research aims to identified development position Karawo embroidery and formulate its marketing strategy in Gorontalo tourist destination. Based on research, the position of Karawo embroidery is in the growth stage. Based on that result, the strategies that can be formulated to improve Karawo marketing in Gorontalo touristdestination are;(1) making advertisement and strengthening the merk, (2) expanding the distribution, (3) increasing product quality through creativity dan innovation, (4) decreasing the product cost, and (5) doing such a big promotion. Keywords:Strategy, Karawo Embroidery, Tourist Destination